Urgent start peritoneal dialysis: Is there room for more? - Ana Rita Marcelino Abrantes; Hernâni Gonçalves; Francisco Alexandre Dina Ferrer; Ana Maria Vila Lobos (Nefrología, 2021)
Background: Despite the increasing prevalence of end-stage renal disease, peritoneal dialysis (PD) is still offered to a minor subset of patients. One way to increment the utilization rates of this technique is the early start of PD after catheter placement, but there are several concerns related to this approach. Methods: Retrospective analysis in a single-center; 52 patients, 34.6% of the patients started in the first 14 days after catheter placement (Urgent start Group – Group 1) and percentage started PD in a conventional mode (Non-urgent start Group – Group 2). Baseline data, short-term (90-day) clinical outcomes, mechanical complications and infectious episodes were compared among Groups. Results: At baseline, Group 1 had an higher Charlson Comobidity Index (CCI). Exchange volumes were significantly lower in Group 1, as expected. Short-term outcomes were equal except for iPTH and albumin, both lower in urgent-start Group (p < 0.05). Episodes of leak, catheter dysfunction and rate of infections were similar among Groups (p > 0.05). In Urgent-start Group we didn’t observed a higher risk for the first peritonitis episode (HR 0.68; 95% CI 0.24–1.99; p > 0.05), higher dropout rate or risk to quit the technique (long rank test, p > 0.05; HR 0.57; 95% CI 0.29–1.13; p > 0.05). Conclusion: According to our observations, urgent-start PD seems to be a valid and safe alternative to urgent hemodialysis with central venous catheter and should be offered to patients without major contraindications. Resumen: Antecedentes: A pesar de la creciente prevalencia de la enfermedad renal terminal, la diálisis peritoneal (DP) sigue ofreciéndose a un reducido subconjunto de pacientes. Una forma de incrementar las tasas de utilización de esta técnica es el inicio temprano de la DP después de la colocación del catéter, pero existen varias dudas respecto a esta estrategia. Métodos: Análisis retrospectivo en un único centro; 52 pacientes; en el 34,6% de los pacientes se inició en los 14 primeros días tras la colocación del catéter (grupo de inicio urgente [grupo 1]) y el resto comenzó la DP de forma convencional (grupo de inicio no urgente [grupo 2]). Se compararon los datos iniciales, los resultados clínicos a corto plazo (90 días), las complicaciones mecánicas y los episodios infecciosos entre los grupos. Resultados: Al inicio del estudio, el grupo 1 tenía un índice de comorbilidad de Charlson (ICC) más alto. Los volúmenes de intercambio fueron significativamente menores en el grupo 1, como se esperaba. Los resultados a corto plazo fueron iguales, excepto para la hormona paratiroidea intacta (HPTi) y la albúmina, ambas inferiores en el grupo de inicio urgente (p < 0,05). Los episodios de fuga y de disfunción del catéter, así como la tasa de infecciones, fueron similares entre los grupos (p > 0,05). En el grupo de inicio urgente no se observó un mayor riesgo de sufrir el primer episodio de peritonitis (CRI: 0,68; IC del 95%: 0,24-1,99; p > 0,05), ni una mayor tasa de abandono o riesgo de abandonar la técnica (prueba del orden logarítmico, p > 0,05; CRI:0,57; IC del 95%: 0,29-1,13; p > 0,05). Conclusión: Según nuestras observaciones, la DP de inicio urgente parece ser una alternativa válida y segura a la hemodiálisis urgente con catéter venoso central, y debería ofrecerse a los pacientes sin contraindicaciones importantes.